EVOLUSI DALAM PEMIKIRAN MANAJEMEN MODERN - Priyawan, Sunu (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
Modern management make more sence when viewed in the light of its foundations; the search for a harmony of people and organizations undertaken by the modern berhaviorists actually began many years ealier. These efforts were directed at a just adapatation of human needs and aspirations to the requirements and goals of the organizatios. â€œHarmonyâ€ means agreement between the part of design or composition that gives a pleasing unity of effect, whether it be in music, art, or organizational life. This article probes the modern quest to resolve the conflict between the logic of efficiency and the logic of sentiments, the search to meet human needs while fulfilling the objectives of the organization.Â Keywords: Human, organisations, management.Â